2020
DOI: 10.2147/cmar.s245726
|View full text |Cite
|
Sign up to set email alerts
|

<p>15-PGDH Expression in Gastric Cancer: A Potential Role in Anti-Tumor Immunity</p>

Abstract: Introduction Host immunity plays a vital role in tumorigenesis, including in tumor invasion and metastasis. However, the precise underlying mechanism remains to be explored. The enzyme 15-PGDH, which plays a key role in prostaglandin degradation, is a critical inflammatory mediator in gastric cancer (GC) tumorigenesis. Materials and Methods Immunohistochemistry was performed to determine 15-PGDH expression in GC and the corresponding adjacent non-neoplastic tissues (n=9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Finally, we identified the up-regulation of PGDH in MIBC tissues. As demonstrated in several studies, the expression of the PGDH has been significantly decreased in various types of cancer tissues which assuming to act as a potential tumor suppressor by inhibiting proliferation and differentiation of cancer cells [ 72 74 ]. While most reports revealed low expression levels of PGDH in different cancers, high expression levels of PGDH have been observed in ovarian cancer [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we identified the up-regulation of PGDH in MIBC tissues. As demonstrated in several studies, the expression of the PGDH has been significantly decreased in various types of cancer tissues which assuming to act as a potential tumor suppressor by inhibiting proliferation and differentiation of cancer cells [ 72 74 ]. While most reports revealed low expression levels of PGDH in different cancers, high expression levels of PGDH have been observed in ovarian cancer [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme 15-PGDH, which plays a key role in prostaglandin degradation, is a critical inflammatory mediator in gastric cancer tumorigenesis. A study with gastric carcinoma patients demonstrated that 15-PGDH may contribute to anti-tumor immunity by regulating FOXP3 (fork head box protein 3) [63]. Also, a study with 277 patients showed that the presence of the prostaglandin PGD 2 reduces tumor expansion of gastric adenocarcinoma by inhibiting the peroxisome proliferator-activated receptor gamma (PPARγ) pathway [36].…”
Section: Prostaglandins In Digestive System and Pancreas Cancermentioning
confidence: 99%
“…14 For breast cancer and gastric cancer patients, the low expression of 15-PGDH is associated with reduced overall survival. 16,17 In addition, the expression level of 15-PGDH is associated with drug resistance. 16 The down-regulated expression level of 15-PGDH is related to tamoxifen resistance and decreases overall survival in ERα-positive breast cancer patients.…”
Section: Introductionmentioning
confidence: 99%